Suppression of Arabidopsis protophloem differentiation and root meristem growth by CLE45 requires the receptor-like kinase BAM3 - Depuydt, Stephen (National Academy of Sciences, 2013)
Peptide signaling presumably occupies a central role in plant development, yet only few concrete examples of receptor-ligand pairs that act in the context of specific differentiation processes have been described. Here we report that second-site null mutations in the Arabidopsis leucine-rich repeat receptor-like kinase gene barely any meristem 3 (BAM3) perfectly suppress the postembryonic root meristem growth defect and the associated perturbed protophloem development of the brevis radix (brx) mutant. The roots of bam3 mutants specifically resist growth inhibition by the CLAVATA3/ENDOSPERM SURROUNDING REGION 45 (CLE45) peptide ligand. WT plants transformed with a construct for ectopic overexpression of CLE45 could not be recovered, with the exception of a single severely dwarfed and sterile plant that eventually died. By contrast, we obtained numerous transgenic bam3 mutants transformed with the same construct. These transgenic plants displayed a WT phenotype, however, supporting the notion that CLE45 is the likely BAM3 ligand. The results correlate with the observation that external CLE45 application represses protophloem differentiation in WT, but not in bam3 mutants. BAM3, BRX, and CLE45 are expressed in a similar spatiotemporal trend along the developing protophloem, up to the end of the transition zone. Induction of BAM3 expression upon CLE45 application, ectopic overexpression of BAM3 in brx root meristems, and laser ablation experiments suggest that intertwined regulatory activity of BRX, BAM3, and CLE45 could be involved in the proper transition of protophloem cells from proliferation to differentiation, thereby impinging on postembryonic growth capacity of the root meristem.